STRATEGI PEMERINTAH KOTA PEKANBARU DALAM PENGEMBANGAN KOTA LAYAK ANAK DI KOTA PEKANBARU TAHUN 2014 - Sri Rahmayuni; Wan Asrida (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2017)
Earth is only one, while behavior is not appreciated cohabitation is a violation of morality that adhering to the norms of human rights as a guide, more specifically, to the recognition and implementation of children's rights as an integral part of human rights.In the protection of human rights, children are also included in it should be protected basic rights as human beings. and as a citizen. The real form of government efforts to ensure child protection is to realize the development of the Regency / City Eligible Children (KLA) in the regions of Indonesia. In 2011, the Ministry of Women's Empowerment and Child Protection (KPPPA) initiated Regency / City Eligible Children (KLA) as a child rights-based development system at the level of district / municipality.The purpose of this study was to determine (1) the government's strategy in the development of Pekanbaru City Pekanbaru City Proper Child in 2014. (2) The obstacles that affect the government's strategy in the development of Pekanbaru City for Children in Pekanbaru.This research is a qualitative approach. This research was conducted in the city of Pekanbaru. The technique used to collect data in this study were (1) interview, (2) Documentation; and (3) Study Library.The conclusion of this study: (1) Strategy adopted by the Government in the development of Pekanbaru City Pekanbaru City Proper Child in 2014 was over three (3) strategies, among others diverfikasi first strategy, innovative strategies, and preventive strategies. (2) The constraints affecting Pekanbaru City Government Strategy in the development of the City Proper Child in Pekanbaru. First, the lack of dissemination to the public. Second, budget constraints, and the third is still a lack of community participation.Keywords: Strategy, Development, City of Eligible Children